Ginsenosides Rb1 Attenuates Chronic Social Defeat Stress-Induced Depressive Behavior via Regulation of SIRT1-NLRP3/Nrf2 Pathways - Jiang, Ning; Zhang, Yiwen; Yao, Caihong; Huang, Hong; Wang, Qiong; Huang, Shuangxue; He, Qinghu; Liu, Xinmin (Frontiers in Nutrition, 2022)
Ginsenoside Rb1, a diol‐type ginseng saponin, has a variety of positive effects on the central nervous system. This study was aimed to investigate the antidepressant effects of Rb1 on chronic social defeat stress (CSDS) induced behavioral deficits and the exact neural cascades linked with inflammatory processes. Behavioral results (social interaction test, tail suspension test and forced swimming test) revealed that oral treatment of Rb1 (35 and 70 mg/kg) alleviates depression-like behavior. Rb1 treatment increased antioxidant enzyme activity (SOD and CAT) and reduced LPO content in the hippocampus. Rb1 also suppressed the production of inflammatory cytokines (TNF-α, IL-6, and IL-1β) as well as microglial activation (Iba1) in response to CSDS. Moreover, Rb1 administration considerably reduced the protein expression of NLRP3 (inflammasome), and promoted the protein expressions of Nrf2, HO-1 and SIRT1 activation in the hippocampus. Collectively, our findings show that Rb1 efficiently restores the depressive-like behaviors of CSDS-induced model mice, are mediated in part through the normalization of the levels of oxidative stress and the suppression of neuroinflammation partly through the regulation of SIRT1-NLRP3/Nrf2 pathways. This study highlights Rb1 as a candidate novel therapeutic agent for the treatment of depression.